Pre and Post Treasury Single Account (TSA) Implementation and the Nigeria’s Macroeconomic Performance - Stephen, Ewiwile,; Sinebe, Michael Tonbraladoh; Mokobia, Ngozi Alison; Agbogun, Oghenekparobo Ernest; Ighoroje, James (Journal of Ecohumanism, 2024)
The paper examined the impact of pre- and post-TSA implementation on Nigeria’s macroeconomic performance. Robust regression estimates were used to analyze the sensitivity of both pre-TSA and post-TSA periods to three macroeconomic performance measures in Nigeria between 2007 and 2014 and 2015 and 2022, respectively. Meanwhile, a paired sample t-test was employed to determine whether the mean values of government total revenue, exchange rate, interest rate, and per capita income differed significantly. The results confirmed that federal government aggregate revenue plays a significant role in influencing Nigeria's macroeconomic performance. Additionally, the mean GTR increased from $8565.95 billion in the pre-TSA period to $9151.93 billion in the post-TSA period. However, this increase was not statistically significant, likely due to delays in TSA implementation. The exchange rate rose significantly, suggesting a notable devaluation of the Nigerian currency. Hence, it is imperative for the government to further strengthen the mechanisms of the TSA.